1996
DOI: 10.1002/masy.19961070131
|View full text |Cite
|
Sign up to set email alerts
|

Use of polyiminophosphazene bases for ring‐opening polymerizations

Abstract: The polyiminophosphazene bases Et‐P2 and t‐Bu‐P4 were used as a promoter for ethylene oxide and siloxane polymerizations. Initiation by an alcohol in combination with t‐Bu‐P4 lead to an extremely rapid polymerization reaction of octamethylcyclotetrasiloxane. In the case of ethylene oxide, well‐defined polymers were obtained, however the rate of polymerization decreased during the polymerization reaction due to decomposition of the counterion. In combination with organolithium compounds, the phosphazene bases l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
67
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 13 publications
2
67
1
Order By: Relevance
“…The substantial increase in temperature needed to obtain the same order of magnitude for k p (2.0 Â 10 À4 and 5.8 Â 10 À4 L Á mol À1 Á s À1 for polymerizations initiated by sodium thiophenolate at 130 8C in DMSO and by the phosphazene/thiophenol system at 60 8C in THF, respectively) clearly demonstrate a higher reactivity of this new initiating system compared to the conventional one. A similar increase in reactivity with phosphazene bases has been already observed for the ROP of cyclic esters, [12] cyclosiloxanes, [8] and ethylene oxide. [8,9] It is now well accepted that the use of a very soft and bulky cation such as [Bu…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The substantial increase in temperature needed to obtain the same order of magnitude for k p (2.0 Â 10 À4 and 5.8 Â 10 À4 L Á mol À1 Á s À1 for polymerizations initiated by sodium thiophenolate at 130 8C in DMSO and by the phosphazene/thiophenol system at 60 8C in THF, respectively) clearly demonstrate a higher reactivity of this new initiating system compared to the conventional one. A similar increase in reactivity with phosphazene bases has been already observed for the ROP of cyclic esters, [12] cyclosiloxanes, [8] and ethylene oxide. [8,9] It is now well accepted that the use of a very soft and bulky cation such as [Bu…”
Section: Resultssupporting
confidence: 64%
“…A similar increase in reactivity with phosphazene bases has been already observed for the ROP of cyclic esters, [12] cyclosiloxanes, [8] and ethylene oxide. [8,9] It is now well accepted that the use of a very soft and bulky cation such as [Bu…”
Section: Resultssupporting
confidence: 64%
See 2 more Smart Citations
“…[12] Recently Eßwein et al showed that in the presence of a strong Lewis base, for example, the phosphazene base Bu t P 4 , polymerization of ethylene oxide with Li þ counterions can be achieved. [13][14][15] In this case the phosphazene base Bu t P 4 forms a strong complex with Li þ resulting in a break up of the strong lithium alkoxide aggregates, and thus making the polymerization of ethylene oxide possible. Furthermore, because of the strongly basic character of the phosphazene base Bu t P 4 even alcohols can be used as initiators.…”
Section: Introductionmentioning
confidence: 99%